Learning Management Systems on Blended Learning Courses: An Experience-Based Observation - Kuran, Mehmet Şükrü; Pedersen, Jens Myrup; Elsner, Raphael (Springer Verlag service@springer.de, 2017)
This paper gives an overview of Learning Management System (LMS) features based on observations on a blended learning course under the Erasmus+ project COLIBRI. We explain the main features of LMSes under two main categories: accessibility content-related and underline the capabilities of four LMSes, Moodle, Blackboard Learn, Canvas, and Stud.IP with respect to these. We explain how these features were utilized to increase the efficiency, tractability, and quality of experience of the course. We found that an LMS with advanced features such as progress tracking, modular course support, interactive content support, and content access restriction is of paramount importance for blended learning courses. © 2017 Elsevier B.V., All rights reserved.
Keywords: Curricula; Image Processing; Quality of Service; Access Restriction; Blended Learning; Interactive Contents; Learning Management System; Quality of Experience (Qoe); Education